An Exploration of the Use of Animated Video Media in Enhancing Students’ Learning Motivation at SMP PAB 1 Klumpang - Tambak, Aminah; Setiawan, Hasrian Rudi; Nurdianti, Nurdianti; Lestari, Sri Putri (Yayasan Rahmat Islamiyah, 2025)
This study aims to explore the use of animated video media in enhancing students’ learning motivation at SMP PAB 1 Klumpang. The research employed a qualitative approach using a case study design. Data were collected through observations, in-depth interviews with teachers and students, and learning documentation. The findings reveal that the use of animated video media increases students’ interest, attention, and active participation in the learning process. Students expressed greater enthusiasm and motivation when the material was presented visually and interactively. Teachers also experienced ease in delivering the material and managing the classroom. Therefore, animated video media is proven to be effective as a learning aid in creating an engaging and motivating learning environment.